Beyond information seeking: a latent profile analysis of financial media repertoires and psychological motivations among Chinese users - Qiren Xiang (Frontiers in Psychology, 2026)
Introduction In the digital era, financial information acquisition is a complex behavioral outcome driven by individual psychological needs and structural constraints. Drawing on the Duality of Media framework and Uses and Gratifications (U&G) theory, this study investigates the cross-platform financial media repertoires of Chinese audiences and unpacks the psychological and structural mechanisms driving these configurations. Methods Based on a survey of 1,002 participants, Latent Profile Analysis (LPA) was employed to identify distinct behavioral patterns. Multinomial logistic regressions, alongside subsample heterogeneity analyses, were conducted to examine how personal factors (including financial knowledge and psychological motivations) and structural factors predict repertoire membership. Results The analysis identified five distinct repertoires: comprehensive Low-Frequency Repertoire, Comprehensive Medium-Frequency Repertoire, Social Media-Centric Repertoire, Comprehensive High-Frequency Repertoire, and Online-Only Repertoire. Repertoire configuration reflects a recursive interplay between individual agency and structural conditions. At the individual level, systematic financial knowledge alongside cognitive and belongingness motivations predicts high-engagement profiles, escapism suppresses active use, and affective motivation acts as a psychological buffer for the adoption of the Social Media-Centric Repertoire. Structurally, high-frequency omnivorous engagement hinges on time availability—supported by workplace hours and low-friction transit—while Online-Only Repertoire adoption is heavily concentrated within core metropolitan centers relative to lower-tier regions. Discussion These findings expand Uses and Gratifications theory into a repertoire ecology framework, delineating spatiotemporal and generational boundary conditions. By illustrating how agency operates within structural bounds, this study provides targeted implications for professional media, digital platforms, and regulators to build an inclusive, balanced financial communication ecosystem.